ASSESSING ENVIRONMENTAL NOISE POLLUTION AROUND PUBLIC HOSPITALS IN SELANGOR, MALAYSIA: IMPLICATIONS FOR URBAN PLANNING - Mohd Nasir, Yusma Hanim; Wan Ismail, Wan Zuriea; Misni, Alamah; Aksah, Hasnizan (PLANNING MALAYSIA, 2024)
Environmental noise is a major concern, particularly in the vicinity of hospitals, which are designated as sensitive areas. There are many complaints about the outside noise, which makes their time in the hospital uncomfortable. Numerous factors, such as expanding urbanisation, industrial activity, traffic, and building, contribute to environmental noise pollution. To avoid having a significant negative effect on users, it is crucial to investigate the sources and measure the level of environmental noise. To date, no data has been recorded on environmental noise around public hospitals in Malaysia. The aim of this study is to assess the current environmental noise pollution surrounding selected hospitals and explore potential improvements that contribute to future urban planning. This study integrates a field measurement at three public hospitals in the Klang Valley (Hospital Shah Alam, Hospital Tengku Ampuan Rahimah and Hospital Sungai Buloh), employing quantitative data collection via a sound level meter with a data logger to identify the various environmental noise sources surrounding public hospitals in the Klang Valley. The findings indicate that in one case study, the average readings failed to meet the DOE standard, categorising it as environmental noise pollution. Considering the results obtained, all three case studies’ environments require significant improvements that can be addressed through strategic urban planning, such as enforcing zoning regulations that restrict noise-emitting activities in the surrounding areas.